Membership Categorisation Analysis. Technologies of social action - Fitzgerald, Richard; Housely, William; Rintel, Sean (Journal of Pragmatics, 2017)
The origin of this special issue was a panel organised at the International Institute of Ethnomethodology and Conversation Analysis (IIEMCA) on Membership Categorisation Analysis (MCA), held at Kolding in Denmark in 2015. The panel, in memory of Stephen Hester who died in 2014, brought together a number of researchers to discuss the current state of the field and present new directions in research in MCA. Building on the pioneering work of Harvey Sacks and the later work of Hester and others the special issue highlights the contemporary development of MCA as a rigorous empirical approach to the study of situated identity within the flow of social interaction. The papers, placed at the intersection between pragmatics and sociology in examining multiple sequentially organised layers of category work, examine the organisation of social knowledge and knowledge entitlement, of moral ordering and the deployment of social norms, but also new and emergent areas of interest around spatial and embodied social action within the frame of technology and technologies of interaction.